Biliteracy development in Mexican primary education: analysing written expression in P'urhepecha and Spanish. Issue 3 (3rd May 2020) - Groff, Cynthia; Bellamy, Kate
ABSTRACT: In the face of immense pressure from Spanish, the national language, a group of educators in Michoacán are committed to prioritising P'urhepecha in two local primary schools where P'urhepecha is the dominant community language. The history of educational initiatives among the P'urhepecha people illustrates the inconsistent and primarily assimilationist educational environment faced by indigenous populations in Mexico, providing context for the schools' efforts, which encourage literacy skills in both languages. We analyse the biliteracy development of a group of 4th grade students, qualitatively analysing written production in both P'urhepecha and Spanish, with a focus on patterns in orthographic conventions, lexicon (including borrowing and language mixing), sentence structure, and morpho-syntactic complexity. The students clearly have more developed writing skills in P'urhepecha than in Spanish, producing longer, more coherent texts in their mother tongue, and using more variation in vocabulary and tenses. Yet in both languages, the students find creative and unconventional ways to represent oral language in writing. Through this initial analysis of 24 student essays, we consider the interrelationship among literacy skills in two languages, the impact of this educational initiative in terms of biliteracy development, as well as practical implications for educational practices at the bilingual schools.